Careers In Sustainability - AR327 - 202301 - Ebermann Vera, Erika (2023)
Description of Course This first-year colloquium will prepare Sustainable Built Environments students with insight into sustainable concepts and practices by immersion in the field of sustainability. With a focus on preparation to enter the sustainability field through creating self-marketing materials, students will explore current sustainability career trends. Course Prerequisites No prerequisites are required for enrollment of this course; however, it is assumed that those taking this course are also taking SBE 195A Careers in Sustainability in the same semester. Global Lecturer (Contact First) Erika Ebermann Vera, Arch. Architect, University Professor of the Architecture Faculty in the UPC. International Specialist in Restoration and Preservation of Buildings Heritage and Sustainable Architecture Email: erikaebermann@email.arizona.edu Office hours by appointment. University of Arizona Faculty Nataliya Apanovich, Ph.D. Lecturer, Sustainable Built Environments Program School of Landscape Architecture & Planning College of Architecture, Planning, and Landscape Architecture Email: apanovich@arizona.edu 1Office hours by appointment.